Structural Relaxation of Salmon Gelatin Films in the Glassy State - Lopez-Angulo, D (Springer, 2015)
The unique property of gelatin to form networks and induce plasticity and elasticity is considered beneficial in the preparation of biopolymer-based packaging materials. However, its use in food products has been limited by some religious groups (Gudmundsson 2002). Gelatins from marine sources have emerged as an alternative, although they are different from mammalian collagen in terms of their biochemical constituents and therefore in their functional properties. It has been shown that cold-water fish collagen can have a lower content of amino acids (~16–18 %) (Gilsenan and Ross-Murphy 2000). Joly-Duhamel et al. (2002) established a positive correlation of the concentration of amino acids, proline (Pro) and hydroxyproline (Hyp), with the melting temperature of native collagen (helix to coil) and gelatin molecular weight with renaturation temperature (coil to helix), suggesting an important effect of biochemical composition on the structure stability of the gel network. An aspect that has not been explored in detail for marine gelatin is the structural stability of these systems at temperatures below their glass transition temperature (Tg). Early studies in glassy carbohydrates by Noel et al. (1999) described the ageing kinetics of maltose in the glassy state in terms of an overshoot in heat capacity on consecutive heating runs using a differential scanning calorimeter (DSC). Badii et al. (2005) evaluated the kinetics of enthalpic relaxation of bovine gelatin state as a function of the difference between ageing temperature and Tg. In their later work, the same authors quantified the enthalpic relaxation of the same model system by DSC, correlating enthalpic values with an increase in the elastic modulus (E) obtained by mechanical spectroscopy. Work by Lourdin et al. (2002) described the mechanical relaxation of amorphous potato starch in the glassy state, obtaining characteristic relaxation parameters by the application of the Kohlrausch–Williams–Watts (KWW) model (Eq. 1). Anderssen et al. (2004) discussed the KWW equation in terms of a spectrum of relaxation times describing the ageing of a polymer. The KWW is an equation that can quantitatively describe the kinetics of the relaxation process toward an absolute relaxed state (Anderssen et al. 2004): (Formula presented) where φ is the relaxation function, t is time, β (0 < β ≤ 1) is the width of the relaxation time distribution spectrum, and τ0 is the characteristic relaxation time, being dependent on temperature and material structure. © 2015, Springer Science+Business Media New York.